Advances in Enantioconvergent Transition-Metal-Catalyzed Cross-Coupling Reactions of Racemic α-Silyl and α-Boryl Reagents - Kranidiotis-Hisatomi, Nektarios; Oestreich, Martin (Synthesis, 2023)
Enantioconvergent transition-metal-catalyzed cross-coupling reactions of racemic α-silyl and α-boryl reagents represent one of the key tools to afford highly enantioenriched α-chiral silanes and boranes. The approach traces back the use of α-silyl nucleophiles, employing palladium precatalysts. More recent work makes use of α-silyl and α-boryl electrophiles under nickel and copper catalysis. The limits of this field have been significantly extended by the design and development of numerous chiral ligands. In this short review, the progress made in this rapidly evolving field is summarized.1 Introduction2 α-Silyl Nucleophiles and Electrophiles2.1 Palladium Catalysis2.2 Nickel Catalysis2.3 Copper Catalysis3 α-Boryl Electrophiles3.1 Nickel Catalysis4 Summary and Outlook
Keywords: asymmetric catalysis; boron; cross-coupling reactions; enantioconvergence; enantioselectivity; silicon